Giant cellular angiofibroma of the vulva: case report - Ribeiro, Ana; Ferreira, Isabel; Ramos, Filomena (Clinical Journal of Obstetrics and Gynecology, 2019)
Cellular Angiofibroma is a rare benign mesenchymal tumor without gender preference. It is usually a small (<3cm), well-circumscribed, mostly asymptomatic and typically slow growing. Surgical removal of the mass with its capsule is the preferred treatment, not only helps guarantee complete excision and prevent its recurrence but also minimize blood loss. We present the case of a 76-year-old woman with a giant vulvar mass.